Applicability of bridge-type pneumatic energy-saving systems and its experimental validation. Issue 5 (May 2020) - Du, Hongwang; Hu, Chaochun; Xiong, Wei; Wang, Lu
Abstract: The bridge-type pneumatic system is to control the intake and exhaust time sequences of an air cylinder with four switch valves by applying the expansion energy of air for work to save energy. However, the system is often sensitive, and thus, the control accuracy can be rather poor. Therefore, the applicability of this system remains to be further tested. A nonlinear dynamic optimization model with the air consumption as the objective function was established. A simultaneous collocation method was used to obtain the on–off time sequences. The concept of optimization performance rating to evaluate the system's energy-saving performance and the stability was introduced. Experiments were done to validate the applicability of the circuit. The results showed that the bridge circuit was applicable to a certain range of working conditions under each given action system and that instability, such as rebound or impact, could occur outside this range. Abstract : Mechanical Engineering; Dynamical System; Mathematical Optimization; Energy Conservation; Fluid Mechanics; Compressed air; bridge-type pneumatic system; energy-saving; dynamic optimization; applicability range